2017
DOI: 10.3390/rs9050508
|View full text |Cite
|
Sign up to set email alerts
|

3D Imaging of Greenhouse Plants with an Inexpensive Binocular Stereo Vision System

Abstract: Nowadays, 3D imaging of plants not only contributes to monitoring and managing plant growth, but is also becoming an essential part of high-throughput plant phenotyping. In this paper, an inexpensive (less than 70 USD) and portable platform with binocular stereo vision is established, which can be controlled by a laptop. In the stereo matching step, an efficient cost calculating measure-AD-Census-is integrated with the adaptive support-weight (ASW) approach to improve the ASW's performance on real plant images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 44 publications
0
40
0
Order By: Relevance
“…Laser sensors: This system is based on light detection and ranging (LiDAR), where laser beams are projected onto plants. The projected laser beams (scattered energy from the plant or the surface) can then be measured using triangulation and a dense 3D map of point clouds is constructed (Kjaer and Ottosen ; Li et al ). This laser sensor approach can measure the distance between sensor and the object, based on the elapsed time between the emission and return of laser pulse from the sensor (the ToF method), or based on trigonometry (Omasa et al ).…”
Section: Genetics Of Barley Shoot Architecturementioning
confidence: 99%
“…Laser sensors: This system is based on light detection and ranging (LiDAR), where laser beams are projected onto plants. The projected laser beams (scattered energy from the plant or the surface) can then be measured using triangulation and a dense 3D map of point clouds is constructed (Kjaer and Ottosen ; Li et al ). This laser sensor approach can measure the distance between sensor and the object, based on the elapsed time between the emission and return of laser pulse from the sensor (the ToF method), or based on trigonometry (Omasa et al ).…”
Section: Genetics Of Barley Shoot Architecturementioning
confidence: 99%
“…For this study, a baseline of 50 mm was used. For the same distance between the cameras and the plants (1 m), Li et al (2017) have shown that a baseline of 80 mm provides the best compromise between depth accuracy and mismatch rate. However, their test took place in indoor conditions.…”
Section: Effect Of Direct Sunlight On Matchingmentioning
confidence: 99%
“…It means that disparities differing from one pixel contributed to the error, with the same weight as a more important error. In comparison with the literature (Scharstein and Szeliski, 2002) and more particularly with an optimized stereo matching algorithm leading to errors of 2.9 % and 7 % for cones and teddy images respectively (Li et al, 2017), the performances of the SGBM algorithm on the Middlebury dataset were considered as sufficient.…”
Section: The Stereo Matching Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…While the stereo-vision system is insensitive to movement and has color information, it also has poor depth resolution and is susceptible to sunlight. A low-cost and portable stereo-vision system was established to realize 3D imaging of plants under greenhouse cultivation [8]. A growth chamber system for 3D imaging by using a 3D-calibrated camera array was successfully used to quantify leaf morphological traits, 2D, and 3D leaf areas, and diurnal cycles of leaf movement; however, the limitation of this system is that it can only acquire half-shelf models, which lack detailed information about overlapping leaves [9].…”
Section: Poor Resolutionmentioning
confidence: 99%